2006 International Electron Devices Meeting 2006
DOI: 10.1109/iedm.2006.346976
|View full text |Cite
|
Sign up to set email alerts
|

Fully Optimized Cu based process with dedicated cavity etch for 1.75μm and 1.45μm pixel pitch CMOS Image Sensors

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…The novel SPAD structure presented in this paper was implemented in a dedicated 130 nm imaging CMOS process [16]. The core of the SPAD consists of a planar p-n junction biased above breakdown, thus operating in Geiger mode.…”
Section: Spad Implementationmentioning
confidence: 99%
“…The novel SPAD structure presented in this paper was implemented in a dedicated 130 nm imaging CMOS process [16]. The core of the SPAD consists of a planar p-n junction biased above breakdown, thus operating in Geiger mode.…”
Section: Spad Implementationmentioning
confidence: 99%
“…12 The pixel architecture is a 4T-type pinned photodiode with 1.75 equivalent shared transistors per pixel. Several doses of metallic contamination were introduced using ion implantation through the sacrificial oxide grown before the gate stack was processed.…”
Section: Methodsmentioning
confidence: 99%
“…During the past few years, research has revealed that the random noise in CMOS imagers is mainly composed out of 1/f and the so-called Random Telegraph Signal (RTS) noise [3]. The dominant noise sources in CMOS image sensors (CIS) are due to the lattice defects at Si-SiO 2 interface of the in-pixel source follower (SF) transistor [4,5].…”
Section: Introductionmentioning
confidence: 99%